1989
DOI: 10.3354/meps058299
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of detritus and bacteria as food sources by two bivalve suspension-feeders, the oyster Crassostrea virginica and the mussel Geukensia demissa

Abstract: The concentration and composition of suspended particulate food available to estuarine suspension-feeding bivalve molluscs varies temporarily and spatially. Non-algal food sources may be important to suspension-feeders when algal concentrations are seasonally low or where there are high concentrations of suspended detrital material and bacteria, as found withln marshes. We carried out a series of laboratory experiments and field measurements to determine to what extent 2 common estuarine bivalve molluscs, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 37 publications
7
115
1
2
Order By: Relevance
“…In the case of mussels, microbial Bt products would be assimilated through food acquisition mechanisms, since the size of Bt spores should fall well within the dimensional range of preferred bivalve food (from about 1 mm to over 90e100 mm; Dame, 1996). This is in agreement with the feeding habits of most marine bivalves, which get their energy from food in the form of particles found in water, including amorphous detritus, small unicellular suspended algae (e.g., phytoplankton) and both auto-and etero-trophic bacteria (Langdon and Newell, 1990;Sarà, 2006Sarà, , 2007a. Our data are, to our knowledge, the first regarding the effect on marine bivalves, and are consistent with findings related to other species, both aquatic and terrestrial.…”
Section: Discussionsupporting
confidence: 83%
“…In the case of mussels, microbial Bt products would be assimilated through food acquisition mechanisms, since the size of Bt spores should fall well within the dimensional range of preferred bivalve food (from about 1 mm to over 90e100 mm; Dame, 1996). This is in agreement with the feeding habits of most marine bivalves, which get their energy from food in the form of particles found in water, including amorphous detritus, small unicellular suspended algae (e.g., phytoplankton) and both auto-and etero-trophic bacteria (Langdon and Newell, 1990;Sarà, 2006Sarà, , 2007a. Our data are, to our knowledge, the first regarding the effect on marine bivalves, and are consistent with findings related to other species, both aquatic and terrestrial.…”
Section: Discussionsupporting
confidence: 83%
“…mostly diatoms, which were not sampled in the present study). This result is consistent with recent Wndings, demonstrating that organic matter of sedimentary origin can be an important component in the diets of many marine suspensivores (Mann 1988;Langdon and Newell 1990;Sarà et al 2002Sarà et al , 2003Sarà 2006), and contradicting the view that phytoplankton is the greatest (or even only) dietary component in coastal habitats (Newell 1979;Loo and Rosenberg 1989). Only in Reykjavik harbour we found extended hard surfaces colonised by a further suspension feeder, the sponge Halichondria panicea.…”
Section: Edulissupporting
confidence: 60%
“…Growth of oysters was always positive, but did not follow the temporal or treatment-related patterns of integrative measures of their phytoplankton prey. Unlike Macoma, growth of the oysters showed no significant relationship to phytoplankton production or biomass, or to particulate N or C. Studies have shown that although oysters can ingest a variety of particle types and sizes, the nutritional value can vary greatly among prey types (e.g., Crosby et al 1990;Newell 1990, 1996;Baldwin and Newell 1991). Growth rates of oysters therefore vary greatly with species and biochemical composition of the available phytoplankton, bacteria, and other particulates.…”
Section: Discussionmentioning
confidence: 99%